Moisturizing Nanoemulgel of Turmeric (Curcuma longa) Rhizome Extract Ameliorates Atopic Dermatitis-like Skin Lesions in Mice Model through Thymic Stromal Lymphopoietin, Interleukin-13, and Interleukin-17 - Nyoman Suryawati; Made Wardhana; I Made Bakta; Made Jawi (Wolters Kluwer - Medknow Publications, 2022)
Introduction: Various moisturizers have been developed for mild and moderate atopic dermatitis (AD). Turmeric (Curcuma longa), containing a potent anti-inflammatory substance, is one of the promising ingredient for moisturizers. By formulating turmeric into nanoemulgel preparation, cutaneous absorption is enhanced. This study aims to determine the effect of 1% turmeric rhizome extract moisturizing nanoemulgel on thymic stromal lymphopoietin (TSLP), interleukin (IL)-13, IL-17 levels, histopathological feature, transepidermal water loss (TEWL) value, and dermatitis score in an AD-like mouse model induced by dinitrochlorobenzene (DNCB). Methods: This study used 35 female BALB/C mice aged 6-8 weeks, weighing 20-30 g. Mice were divided into the treatment group (DNCB and 1% turmeric rhizome extract moisturizing nanoemulgel) and the control group (DNCB and vehicle gel). The DNCB application was carried out twice a week, from day 14 to day 29. On day 30, skin tissue samples were taken to examine TSLP, IL-13, IL-17 levels, and histopathological examination. Results: The treatment group showed lower TSLP, IL-13, and skin tissue IL-17 levels than the control group (P < 0.05). In addition, applying 1% turmeric rhizome extract, moisturizing nanoemulgel improved the treatment group's dermatitis score and histopathological features compared to the control group (P < 0.05). The 1% turmeric extract moisturizing nanoemulgel decreased the TEWL but was statistically insignificant compared to the control group (P > 0.05). Conclusions: Applying 1% turmeric rhizome extract moisturizing nanoemulgel ameliorates AD-like skin lesions by decreasing TSLP, IL-13, and IL-17 levels in the DNCB-induced BALB/c mouse model.